Highly potent fentanyl analogs: apnea from exposure to small quantities of ß-hydroxyfentanyl and furanylfentanyl. (2nd September 2019) - Hendrickson, Robert G.; Akpunonu, Peter; Hughes, Adrienne R.; Gerona, Roy
Abstract: Context: Fentanyl analogs are synthetic opioids that bind to mu receptors with high potency. We report two cases where users developed apnea and required naloxone reversal after exposure to small quantities of the fentanyl analogs, furanylfentanyl and ß-hydroxyfentanyl. Case details: A 19 year-old woman reported insufflating a small number of granules of "fentanyl" powder and developed apnea. A 22 year-old woman touched her tongue to powdered "fentanyl" to treat a migraine headache and became apneic. Results: Furanylfentanyl was identified in the first patient's serum (3.6 ng/mL furanylfentanyl), urine (17.6 ng/mL furanylfentanyl), and in the product (109mg/g powder). ß-hydroxyfentanyl was detected in the second patient's serum (6.5 ng/mL ß-hydroxyfentanyl) and in the product (120 mg/g powder). Discussion: In both cases, furanylfentanyl and ß-hydroxyfentanyl were identified in the serum/plasma and urine. Fentanyl analogs were detected in the product at 109-120mg per gram of powder, which suggests that a 500mcg dose of fentanyl analog is the equivalent to 4.17–4.59mg of powder, or about the mass in 1/500th of a packet of sugar. Unique aspects of these cases are the rarely reported use of furanylfentanyl and ß-hydroxyfentanyl, intentional insufflation of "fentanyl" for therapeutic and recreational use, the small quantities of powder ingested, and the use of non-targeted analysis to identify the fentanyl analogs.